Isomerization of fenbuconazole under UV‐visible irradiation – chemical and toxicological approaches. (8th June 2015) - Lassalle, Yannick; Nicol, Edith; Genty, Christophe; Bourcier, Sophie; Bouchonnet, Stéphane
Abstract : Rationale: Fenbuconazole is a fungicide commonly used for the protection of vineyards, vegetables and grain crops. Under UV‐visible irradiation, it undergoes isomerization through various cyclization processes. Isomeric structures were elucidated by liquid chromatography/high‐resolution multiple‐stage mass spectrometry (LC/HR‐MS n ) coupling. The potential toxicities of these isomers were estimated by in silico tests. Methods: Aqueous solutions of fenbuconazole and grapes treated with this fungicide were irradiated in a self‐made reactor equipped with a mercury vapor lamp. Analyses were carried out using high‐performance liquid chromatography (HPLC) coupled with Fourier transform ion cyclotron resonance mass spectrometry (FT‐ICRMS). High‐resolution m/z measurements, multiple‐stage mass spectrometry and isotopic labeling experiments allowed structural elucidation of the isomers of fenbuconazole. In silico toxicity estimations were carried out using the T.E.S.T. program. Results: Seven isomers of fenbuconazole were detected after irradiation of the fungicide in aqueous solution; the major ones were also detected in the flesh of treated grapes irradiated under laboratory conditions. Elucidation of their chemical structures owing to high resolution measurements and multi‐stage collision induced dissociation experiments allowed confirmation of photo‐transformation pathways mainly dominated by cyclization processes. Photo‐induced isomers exhibited higher potential toxicities than fenbuconazole for Daphnia magna and fathead minnow species. Conclusions: UV‐visible irradiation of fenbuconazole in aqueous solution and on grapes leads to the formation of isomers, all of which being potentially much more toxic than the parent fungicide. Copyright © 2015 John Wiley & Sons, Ltd.